Cadres Empowerment as A Strategy Realizing A Stroke-Free Village - Daning Widi Istianti; Nimsi Melati (FKM UIN Sumatera Utara Medan, 2024)
Stroke is one of the complications of hypertension. Stroke in Indonesia is the third most deadly disease after heart disease and cancer. The community has an important role in improving health by preventing and promoting health, especially cadres. Preliminaries on the Wirogunan showed that cadres needed assistance in realizing a stroke-free village. The purpose of this community service is to improve cadre skills and awareness in preventing hypertensive complications through screening training and increasing cadres' confidence in providing information to the community with hypertension so that it does not develop into a stroke. The implemented activities include identifying the problems through focus group discussion, introducing strokes, screening training, cadre assistance, and evaluation. There were 23 cadres participating in this activity from RW 8, 9, and 10. The results of community service showed that there is an increase in cadre knowledge, increased skills in conducting screening, and increased self-confidence in cadres in providing education to the community. This program is expected to be carried out in an integrated manner with other sectors to reduce the number of people with stroke.